2018
DOI: 10.4162/nrp.2018.12.6.521
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable intakes in relation to behavioral outcomes associated with a nutrition education intervention in preschoolers

Abstract: BACKGROUND/OBJECTIVESAlthough a lot of effort has been put into increasing fruit and vegetable intakes in preschool children, vegetable intake in this group is still low. This study investigated whether nutrition education focusing on fruit and vegetable intakes can affect preschoolers' fruit and vegetable intakes as well as their behavioral outcomes.SUBJECTS/METHODSThirty-five preschoolers (54.3% boys, n = 19) aged 4–6 years residing in Seoul underwent weekly nutrition education intervention (8 sessions) betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
1
10
0
2
Order By: Relevance
“…Several nutrition education programs have reduced unhealthy dietary behaviors in young children in Korea [12,13,14]. Improvements in the nutrition knowledge score [12], nutritional status balance, and regular diet with a higher frequency of consumption of white milk [13] were shown after the nutritional education.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several nutrition education programs have reduced unhealthy dietary behaviors in young children in Korea [12,13,14]. Improvements in the nutrition knowledge score [12], nutritional status balance, and regular diet with a higher frequency of consumption of white milk [13] were shown after the nutritional education.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, vegetables & fruits (V/F) consumption and healthy eating behaviors were higher in the education group than in the control group. Another previous study reported an improvement of fruit and vegetable intakes as well as preschool children’s emotional and behavioral outcomes after nutrition education [14]. Therefore, school-based nutritional education needs to be considered in ECES.…”
Section: Introductionmentioning
confidence: 99%
“…Pada masa ini, pertumbuhan dan perkembangan anak terus berlangsung. Aspek penting dalam perkembangan anak adalah kebiasaan makan (Santrock, 2016) dengan mengkonsumi makanan bergizi seimbang karena dapat mempengaruhi kehidupan selanjutnya (Choi et al, 2018). Namun, umumnya pada masa ini anak memiliki masalah kesehatan.…”
Section: Pendahuluanunclassified
“…Dampak positif yang didapatkan dengan mengkonsumsi buah dan sayuran telah banyak dilaporkan bahwa berdampak bagi kesehatan mental anak-anak hingga dewasa (Choi et al, 2018). Hal ini disebabkan karena buah dan sayuran mengandung banyak unsur gabungan dari beragam vitamin, mineral, maupun antioksidan yang sangat dibutuhkan anak pada pada masa pertumbuhan dan perkembangan (Bean, 2007).…”
Section: Hasil Dan Pembahasanunclassified
“…The data from the research conducted by Paboyo (2012) showed that only 29.6% of preschoolers in Canada consume fruits and vegetables which in accordance with food guidelines in Canada. In the United States of America, at 2014, 31.5% of preschoolers consumed vegetables and fruits less than the recommendation of adequacy while 80.3% consume less vegetable (Krebs, 2010 in Harnack, et al, 2012, D. Upton, 2012, Kirsten, 2014, Eun. 2018.…”
Section: Introductionmentioning
confidence: 99%